Sensitivity of Macroeconomic Policy Goals to Trilemma and Quadrelimma Choices - Kaur, Ramandeep (Asian Development Policy Review, 2019)
This study aims to check the effect of trilemma and quadrilemma choices on price and output stability of the Indian economy over the period of 1980-2016. All the three combos of trilemma triangle have been put into an empirical framework in order to check their effect upon the inflation rate, growth rate, inflation volatility, and output volatility. The role played by the international reserve hoarding has also been taken into account as the many studies have proved that trilemma framework is converting into the quadrilemma due to an increasing amount of reserves as well as due to the decisive role played by these reserves in the effectiveness of trinity choices upon the macroeconomic stability. The Autoregressive Distributed Lag Model (ARDL) has used and concluded that trinity choices could successfully affect the macroeconomic stability of the Indian economy. Another important conclusion is that the quadrilemma framework choices are better than the trilemma as the presence of interaction variable of the trinity indices and international reserves have altered the policy effects in an efficient manner and made these policy choices more stabilizing.